1979
DOI: 10.1159/000232376
|View full text |Cite
|
Sign up to set email alerts
|

Use of Glutaraldehyde-Modified Timothy Grass Pollen Extract in Nasal Hyposensitisation Treatment of Hay Fever

Abstract: 12 patients suffering from grass pollen hay fever were treated for 14 weeks pre- and co-seasonally by intranasal self-administration of an aqueous solution of a glutaraldehyde-treated timothy grass pollen allergen. These patients had a statistically significant decrease in nasal symptom scores during the grass pollen peak period and in nasal challenge end-point titre after the season compared to placebo-treated patients. No significant effect was seen on the eye symptoms. 1 patient withdrew from the trial as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Detection of IgE-reactive components in the systemic circulation when an allergenic extract is given intranasally introduces a new element of discussion about the possible mechanisms by which this form of treatment, recently proposed as an alternative to the parenteral route, produces clinical efficacy in rhinitic patients (15,19,21,30,33). Various hypotheses have been put forward: a common finding in allergic patients after local therapy is a rise in the threshold value as determined by specific provocation tests at the target organ, while the induction of local immunological protection (IgA and IgG blocking antibodies) is suggestive, but results are still contradictory (12,15). Recent studies in mice and rats showed that repeated inhalation of aerosols containing egg albumin or ragweed antigens induced a transient IgE response which switched oii spontaneously despite continuous exposure (10,13,26).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of IgE-reactive components in the systemic circulation when an allergenic extract is given intranasally introduces a new element of discussion about the possible mechanisms by which this form of treatment, recently proposed as an alternative to the parenteral route, produces clinical efficacy in rhinitic patients (15,19,21,30,33). Various hypotheses have been put forward: a common finding in allergic patients after local therapy is a rise in the threshold value as determined by specific provocation tests at the target organ, while the induction of local immunological protection (IgA and IgG blocking antibodies) is suggestive, but results are still contradictory (12,15). Recent studies in mice and rats showed that repeated inhalation of aerosols containing egg albumin or ragweed antigens induced a transient IgE response which switched oii spontaneously despite continuous exposure (10,13,26).…”
Section: Discussionmentioning
confidence: 99%
“…So far, 21 studies are available for LNIT, and 14 of them were properly performed (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), Of these, 13 report a significant improvement of rhinitic symptoms. Furthermore, a reduction of the nasal reactivity and local immunologic response was found in some studies, while systemic immunologic changes were usually absent or equivocal: this may suggest that LNIT exerts its actions only on the target organ.…”
Section: Experimental Evidence: Clinical Efficacymentioning
confidence: 99%
“…As, for traditional subcutaneous immunotherapy, the mechanism of LNIT is still unclear, some immunological modifications were observed during the treatment. An increase of specific secretory IgA and IgG was reported by several authors (9,10,14,21,22), but without any clinical and immunological correlation (9,10,21). A systemic immunological action could be hypothesized by the increase of serum specific IgE, reported after the treatment with intranasal aqueous extract (9,21) and by the relevant allergenic activity observed in animal models after intranasal treatment with allergen in powder form (36).…”
Section: Mechanisms Of Actionmentioning
confidence: 95%